Molecular phylogeny of the spoonbills (Aves: Threskiornithidae) based on mitochondrial DNA - Chesser, R. Terry; Yeung, Carol K. L.; Yao, Cheng-Te; Tian, Xiu-Hua; Li, Shou-Hsien (Zootaxa, 2010)
Spoonbills (genus Platalea) are a small group of wading birds, generally considered to constitute the subfamily Plataleinae (Aves: Threskiornithidae). We reconstructed phylogenetic relationships among the six species of spoonbills using variation in sequences of the mitochondrial genes ND2 and cytochrome b (total 1796 bp). Topologies of phylogenetic trees reconstructed using maximum likelihood, maximum parsimony, and Bayesian analyses were virtually identical and supported monophyly of the spoonbills. Most relationships within Platalea received strong support: P. minor and P. regia were closely related sister species, P. leucorodia was sister to the minor-regia clade, and P. alba was sister to the minor-regia-leucorodia clade. Relationships of P. flavipes and P. ajaja were less well resolved: these species either formed a clade that was sister to the four-species clade, or were successive sisters to this clade. This phylogeny is consistent with ideas of relatedness derived from spoonbill morphology. Our limited sampling of the Threskiornithinae (ibises), the putative sister group to the spoonbills, indicated that this group is paraphyletic, in agreement with previous molecular data; this suggests that separation of the Threskiornithidae into subfamilies Plataleinae and Threskiornithinae may not be warranted.